The relationship between apparent soil electrical conductivity and soil properties Relação entre condutividade elétrica aparente e propriedades do solo - Domingos Sárvio Magalhães Valente; Daniel Marçal de Queiroz; Francisco de Assis de Carvalho Pinto; Nerilson Terra Santos; Fábio Lúcio Santos (Revista Ciência Agronômica, 2012)
Precision agriculture that is based on the physical and chemical properties of soil requires a dense sampling to evaluate spatial variability in the field. This dense sampling is often expensive and time consuming. One technique to reduce the number of samples is to define management zones based on information that is collected in the field. Some researchers have demonstrated the importance of the electrical properties of soil in defining management zones. Thus, the objective of this study was to evaluate the relationship between the apparent soil electrical conductivity and soil properties in mountainous areas of coffee production. The electrical conductivity of soil was evaluated at soil depths ranging from 0.00-0.20 m (EC20) and 0.00-0.40 m (EC40) using a portable meter. The mean values of EC20 and EC40 were 1.80 mS m-1 and 1.22 mS m-1, respectively. Both EC20 and EC40 exhibited comparatively low correlations with the soil properties, whereas higher correlations were obtained for measurements of remaining phosphorus, wherein values of 0.427 and 0.465, respectively, were obtained. A agricultura de precisão baseada nas propriedades físicas e químicas do solo exige uma amostragem densa para se determinar a variabilidade espacial no campo. Essa amostragem densa, muitas vezes apresenta custo e tempo consumido elevado. Uma das técnicas para reduzir o número de amostras é definir zonas de manejo em função de informações coletadas no campo. Alguns pesquisadores têm demonstrado a importância desempenhada pelas variáveis elétricas do solo para definir zonas de manejo. Dessa forma, este trabalho teve como objetivo avaliar a relação entre a variabilidade espacial da condutividade elétrica aparente e propriedades do solo em regiões de produção de cafés de montanha. A condutividade elétrica foi medida no perfil de solo de 0,00-0,20 m (CE20) e 0,00-0,40 m (CE40) usando um sensor portátil. Os valores de CE20 e CE40 foram de 1,80 mS m-1 e 1,22 mS m-1, respectivamente. Ambas CE20 e CE40 apresentaram baixa correlação com as propriedades químicas e a textura do solo, sendo que, a correlação mais elevada foi obtida para o fósforo remanescente com valores de 0,427 e 0,465, respectivamente.